Current Concepts in the Management of Patellofemoral Pain Syndrome - Martínez-Cano, Juan Pablo; Rojas-Canizales, Sebastián; Cortés-Cabrera, Sergio (Revista Colombiana de Ortopedia y Traumatología, 2022)
Introduction: Patellofemoral pain syndrome (PFPS) is one of the leading causes of knee pain, manifesting itself during daily life activities. This study presents a review on PFPS treatment modalities. Materials and methods: State of the art review on the treatment of PFPS with grades of recommendation. Active and passive conservative interventions are reviewed, as well as surgical alternatives. Results: Hip and lower-limb muscle strengthening and stretching are active interventions that provide long-lasting benefits. Passive interventions include patellofemoral joint bracing, kinesiotaping and foot orthoses, and are considered useful coadjuvants to active interventions, with quick relief for patients but usually in the short term. Surgical treatment is only recommended in a small subset of patients with specific anatomic abnormalities in the patellofemoral joint. Discussion: Conservative treatment remains as the mainstream in the management of patellofemoral pain syndrome. Level of Evidence: IV, Clinical Review.